SELF ADJUSTMENT IN ACHIEVING PSYCHOLOGICAL WELL-BEING IN ODAPUS (PERSONS WITH LUPUS) - Sofa, Salsabila Nurmala; Darmawanti, Ira (Character Jurnal Penelitian Psikologi, 2023)
This research uses a qualitative method with a case study approach to find out how people with lupus (odapus) make adjustments to achieve psychological well-being. This data collection technique uses semi-structured interviews and is analyzed using thematic analysis techniques. This study succeeded in revealing based on the theory of self-adjustment, namely self-acceptance, habits and skills. Additional themes for people with lupus to adapt are limiting activities and positive thinking. Meanwhile, in achieving a psychological well-being in lupus sufferers in accordance with the theory of psychological well-being, namely by means of self-acceptance, life goals, and positive relationships with others. Factors that influence the psychological well-being of research participants are social support and self-awareness. This research shows that individuals with lupus have their own way of achieving psychological well-being.